Pengembangan Buku Ajar Ilmu Pengetahuan Alam Berbasis Higher Order Thinking Skill untuk Siswa Sekolah Dasar - Maptuhah Maptuhah; Asep Saefurrohman; Wida Rachmiati (Mafa Press in Collaboration with PGMI Tarbiyah Faculty IPMAFA, 2023)
The aim of this research to knowing the development procedures, feasibility and effectiveness of textbooks to improve the higher order thinking skills grade V SD/MI students. This research uses the Research and Development (R&D) research method and the research model used is the 4D model. Based on the results of the research, the development procedure is carried out referring to the 4D model which has 4 steps, namely Define, Design, Develop, and Disseminate. The results of the analysis of the validation sheets of material experts and media experts, the average score of the product is 87% (very good) and 79% (good) respectively, meaning that the product has been judged